Peran Influencer sebagai Opinion Leader dalam Era Komunikasi Digital - Alfa Risqi Firmansyah; Khofifah Skholihatun Ni’mah; Virda Maulidina Riyanto (GLOBAL SCIENTS PUBLISHER, 2026)
Zakat, this study aims to analyze the representation of opinion leaders in the digital era through a case study of Gerald Vincent’s educational communication strategy, particularly focusing on his communication style and language use in influencing audiences. This research employs the Two-Step Flow of Communication theory and Source Credibility theory to explain the role of influencers in the information dissemination process. The method used is qualitative, involving an analysis of social media content and audience responses. The findings indicate that the communication strategies applied include the use of simple language, structured delivery, and support from facts or data. A communicative and easily understandable language style makes the message more effectively received by the audience. In addition, consistency and clarity in delivering information enhance the influencer’s credibility. The implications of this study suggest that a simple and clear educational communication style can strengthen the role of influencers as opinion leaders in helping audiences understand information in the digital era